SPECIFIC PROPERTIES OF THE DRUG THERAPY FOR STABLE ANGINA IN MEN - R. G. Oganov; G. Ya. Maslennikova (Кардиоваскулярная терапия и профилактика)
According to population studies the prevalence of angina increases with age and is about 4–7% in 65–84 years old men. In drug therapy, except direct action of the medicaments on symptoms and complications of the disease, sexual activity must be taken into account due to its impact on life quality and treatment compliance. Beta-adrenoblockers and sartans are common solution for angina with its usual cardiovascular comorbities. The most selective beta-blocker nebivolol and valsartan do not affect and even increase sexual activity, making them a choice for the treatment of angina in men.